2015
DOI: 10.3390/v7122957
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus gB: A Finely Tuned Fusion Machine

Abstract: Enveloped viruses employ a class of proteins known as fusogens to orchestrate the merger of their surrounding envelope and a target cell membrane. Most fusogens accomplish this task alone, by binding cellular receptors and subsequently catalyzing the membrane fusion process. Surprisingly, in herpesviruses, these functions are distributed among multiple proteins: the conserved fusogen gB, the conserved gH/gL heterodimer of poorly defined function, and various non-conserved receptor-binding proteins. We summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 128 publications
2
90
0
Order By: Relevance
“…This supports the idea that gH or gH/gL activates, rather than represses, gB fusion activity. In accordance with this it has been found that HSV-1 gH comes into close proximity to gB only after binding of gD to one of its receptors, suggesting that gB and gH/gL do not constitutively interact (9,53). Furthermore, it is conceivable that activation of gH 32/98 by receptor-bound gD is impaired, thereby preventing subsequent activation of wild-type gB, whereas mutated gB B4.1 can be activated by gH 32/98 in a gD-independent manner.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This supports the idea that gH or gH/gL activates, rather than represses, gB fusion activity. In accordance with this it has been found that HSV-1 gH comes into close proximity to gB only after binding of gD to one of its receptors, suggesting that gB and gH/gL do not constitutively interact (9,53). Furthermore, it is conceivable that activation of gH 32/98 by receptor-bound gD is impaired, thereby preventing subsequent activation of wild-type gB, whereas mutated gB B4.1 can be activated by gH 32/98 in a gD-independent manner.…”
Section: Discussionsupporting
confidence: 74%
“…Receptor binding leads to conformational changes in the C-terminal region of the HSV-1 gD ectodomain (4,5). According to the current model, this conformational rearrangement of gD induces interaction with the gH/gL complex, which in turn is thought to activate the bona fide fusion protein gB to execute membrane fusion (6)(7)(8)(9). While gD signaling is generally required for triggering membrane fusion in HSV, PrV gD is dispensable for direct cell-to-cell spread and in vitro cell fusion (10)(11)(12).…”
mentioning
confidence: 98%
“…The N122D replacement may result in a destabilization of the gDnectin-1 protein-protein interface due to conformational changes in the globule of the gD protein. Destabilization of the nectin-1-gD-122D protein-protein interface may change the flexibility of gD, thus affecting specific structural rearrangements needed for the downstream interaction of the gD C terminus with glycoproteins gB and gH/gL that is essential for cell entry (31,67,99,100). Making mutant viruses that have changes in the predicted amino acids will indicate whether the predictions are accurate.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction triggers a conformational change in gD, which has been proposed to be important for the activation of the gH-gL complex [44]. Once activated, this complex could then activate gB, which is considered to be the executor of membrane fusion [45,46]. Due to their importance for HSV entry, the protein-protein interactions that take place between the different viral glycoproteins that execute membrane fusion are a good target for the design of novel antivirals that could specifically block these interactions to block virus entry.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the gB-derived peptides might interact with upstream components of the entry cascade. Since the interactions between gH-gL are necessary to trigger gB for membrane fusion, these peptides might be acting as competitive inhibitors, preventing the activation of gB [46]. …”
Section: Discussionmentioning
confidence: 99%